Bi-Phenotypic Trait May Be Conferred by Multiple Alleles in a Germplasm Population - Liu, Fangdong; He, Jianbo; Wang, Wubin; Xing, Guangnan; Gai, Junyi (Frontiers in Genetics, 2020)
The Chinese soybean germplasm pool (CSGP) comprises annual wild (WA), farmers’ landrace (LR) and released cultivar (RC) populations, and ecoregion subpopulations in WA/LR/RC (ecoregion IV/III/II/I). A representative sample consisted of 1,024 accessions was studied for pubescence color (PC) and flower color (FC). In the evolution from WA (brown PC and mainly purple FC) to LR then to RC, with above wild characteristic changed, while gray PC and white FC emerged and their frequency increased. Using 36,952 genomic SNPLDB markers with 100,092 haplotypes, the association between markers and bi-phenotypic traits was detected using χ2 association analysis under single locus model and RTM-GWAS procedure under multi-locus model, respectively. Multiple markers co-associated with individual bi-phenotypic trait with the most significant markers containing multiple rather than two haplotypes even for a bi-phenotypic trait. On a marker/locus, each haplotype corresponds to two colors, except one (FC-1-5) out of 11 haplotypes for single color. The major candidate gene was annotated with its alleles identified from the population sequencing data. Similarly, multiple alleles identified and each corresponds to two colors except three (a8/a9/b3) out of 12 alleles for single color. The major haplotypes/alleles in LR and RC were traced to WA ecoregion subpopulations, the WAIV and WAIII genotypes showed genetically more close to the cultivated subpopulations, therefore, WA from Ecoregion IV and III were inferred as the common ancestor for cultivated soybeans. The marker haplotypes/gene-alleles not exactly coincided with the bi-phenotypic trait has challenged to the traditional Mendelian genetics, which was discussed and to be further studied.